2008
DOI: 10.1161/hypertensionaha.107.103648
|View full text |Cite|
|
Sign up to set email alerts
|

Interference With PPARγ Signaling Causes Cerebral Vascular Dysfunction, Hypertrophy, and Remodeling

Abstract: Abstract-The transcription factor PPAR␥ is expressed in endothelium and vascular muscle where it may exert antiinflammatory and antioxidant effects. We tested the hypothesis that PPAR␥ plays a protective role in the vasculature by examining vascular structure and function in heterozygous knockin mice expressing the P465L dominant negative mutation in PPAR␥ (L/ϩ). In L/ϩ aorta, responses to the endothelium-dependent agonist acetylcholine (ACh) were not affected, but there was an increase in contraction to serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 29 publications
11
102
1
Order By: Relevance
“…PPAR␥ plays a critical role in protecting blood vessels (33), and interference with PPAR␥ signaling produces cerebral arteriolar endothelial dysfunction via a mechanism involving oxidative stress. The end result is cerebral vascular hypertrophy and inward remodeling (7). Thus the decrease in endothelial function in cerebral arterioles may result from a decrease in vasoprotective mechanisms rather than an increase in oxidative stress or inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR␥ plays a critical role in protecting blood vessels (33), and interference with PPAR␥ signaling produces cerebral arteriolar endothelial dysfunction via a mechanism involving oxidative stress. The end result is cerebral vascular hypertrophy and inward remodeling (7). Thus the decrease in endothelial function in cerebral arterioles may result from a decrease in vasoprotective mechanisms rather than an increase in oxidative stress or inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism by which HO-1 inhibits endothelial injury via cilostazol is not fully understood, some studies suggested that PPAR activity might have anti-inflammatory and vasculoprotective benefits [23,[30][31][32]. Thus, it was hypothesized that the cytoprotective effect of HO-1 against inflammatory cytokine-induced endothelial injury is dependent on PPAR activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PPAR-γ has a protective role in vascular function and structure via anti-inflammatory, anti-fibrotic, and antioxidant actions (35,36). Recent studies have shown that telmisartan has an ameliorative effect on endothelial dysfunction by improving the PPAR-γ-eNOS system in Dahl salt-sensitive hypertensive rats (37) or NO bioavailability in Watanabe heritable hyperlipidemic rabbits (38).…”
Section: Discussionmentioning
confidence: 99%